The Influence of Locus of Control and Financial Knowledge of the Millennial Generation on Financial Management Behavior Moderated by Income (Study of Education Personnel at the Universitas Pendidikan Indonesia) - Ruhiat, Jemi Angga; Rohendi, A; Andriani, Rian (The International Journal of Business Review (The Jobs Review), 2023)
This research evaluates the influence of Locus of Control and financial knowledge on the financial management behavior of the millennial generation of education staff at the Universitas Pendidikan Indonesia (UPI). The sample consisted of 240 people, selected through purposive sampling with age criteria of 27-42 years. Data analysis used multiple linear regression and the Moderated Regression Analysis (MRA) interaction test with SPSS. The research results show that Locus of Control, financial knowledge, and income positively affect the financial management behavior of the millennial generation. Locus of Control and financial knowledge also positively influence financial behavior. Income acts as a moderator, strengthening the relationship between Locus of Control, financial knowledge, and financial management behavior. In conclusion, Locus of Control, financial knowledge, and income are important in influencing the financial management behavior of millennial generation students at UPI.